2023
DOI: 10.1186/s10194-023-01547-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of migraine: where are we now?

Abstract: Migraine is a complex brain disorder explained by the interaction of genetic and environmental factors. In monogenic migraines, including familial hemiplegic migraine and migraine with aura associated with hereditary small-vessel disorders, the identified genes code for proteins expressed in neurons, glial cells, or vessels, all of which increase susceptibility to cortical spreading depression. The study of monogenic migraines has shown that the neurovascular unit plays a prominent role in migraine. Genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 191 publications
1
39
0
Order By: Relevance
“…Migraine is predominant in females, peaks in productive age, and is a leading cause of disability among adults [4]. This complex condition is linked to genetic predisposition [5] and is affected by environmental factors [6]. A hyperresponsive brain, together with alterations in peripheral and central sensory processing, are proposed to underlie migraine [7] and its manifestation [8,9].…”
Section: Migrainementioning
confidence: 99%
“…Migraine is predominant in females, peaks in productive age, and is a leading cause of disability among adults [4]. This complex condition is linked to genetic predisposition [5] and is affected by environmental factors [6]. A hyperresponsive brain, together with alterations in peripheral and central sensory processing, are proposed to underlie migraine [7] and its manifestation [8,9].…”
Section: Migrainementioning
confidence: 99%
“…A recent cross-sectional study found that MDD was strongly associated with the frequency and severity of attacks of migraine with aura, a subtype of migraine (11). Furthermore, in genetics, the importance of shared genetic factors between migraine and depression has been acknowledged (12). Although MDD and migraine are frequently seen together, their connection has not been thoroughly established.…”
Section: Introductionmentioning
confidence: 99%
“…FHM is most often an autosomal dominant trait [5]. The three rst identi ed genes all encode ion channels or transporters.…”
Section: Introductionmentioning
confidence: 99%
“…CACNA1A on 19p13 (FHM1-MIM 301011) encodes the pore-forming subunit of neuronal voltage-gated calcium channels Ca V 2.1; ATP1A2 on1q23 (FHM2 -MIM 182340) encodes the catalytic subunit of a sodium/potassium ATP-dependent pump mainly expressed in astrocytes, and SCN1A on 2q24 (FHM3 -MIM 182389) codes for the pore-forming subunit of neuronal voltage-gated sodium channels Na V 1.1. [3,5]. Study of murine models have shown that FHM variants in CACNA1A, ATP1A2 and SCN1A facilitated the initiation of cortical spreading depression waves, the surrogate of migraine aura [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation